Hubungan Durasi Penggunaan Gadget, Pola Asuh Dan Pengawasan Orang Tua Dengan Kecanduan Gadget Pada Anak Usia Dini Di TK Negeri Pembina Ranomeeto - Asrianti Asrianti; Hariati Lestari; Fifi Nirmala G (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Humans are social creatures, they will always have social contact and communication. Gadgets are one of the most advanced communication tools available today. The use of gadgets by Indonesian youth has been increasing every year, reaching 38% in 2011, 72% in 2015, and again increasing 80% in 2015. Children use gadgets to play at least once a week, and some use them several times a week. As they get older and enter puberty, they use gadgets more frequently. Children aged between 10 and 14 years old will use their gadgets more often each week-from 8 to 15 hours. The method in this study is quantitative with observational correlation with a cross sectional approach. The population in this study were 86 students of TK Negeri Pembina Ranomeeto. The sample in this study were 70 students. The sampling technique in this study was using random sampling technique with data collection method using questionnaire. The findings of this investigation show that there is a relationship between parenting (0.018) and parental supervision (0.036) with gadget addiction in early childhood, and there is no relationship between the duration of gadget use (0.108) with gadget addiction in early childhood at TK Negeri Pembina Ranomeeto Year 2023. Children can easily get addicted to gadgets because they are still too young to make decisions.